Atlas of lymph node pathology - Miranda, Roberto N. (Atlas of Anatomic Pathology, 2013)
Atlas of Lymph Node Pathology reviews the histopathology of nodal diseases, illustrating the use of ancillary studies and includes concise discussions of pathogenesis, clinical settings and clinical significance of the pathologic diagnosis. The atlas features an overview of the benign reactive processes secondary to infectious, environmental or unknown insults, as well as relevant illustrations of virtually all primary and secondary neoplasms involving lymph nodes. The atlas also includes macroscopic images of some disorders, tables that help readers understand and comprehend diseases that look alike, and diagnostic algorithms for certain groups of diseases. Authored by highly experienced pathologists, Atlas of Lymph Node Pathology is a valuable resource that illustrates the vast majority of diseases practicing pathologists, clinicians and oncologists are likely to encounter in daily practice.